2008
DOI: 10.1007/s10440-008-9388-y
|View full text |Cite
|
Sign up to set email alerts
|

Solvability of a Mixed Nonlocal Problem for a Nonlinear Singular Viscoelastic Equation

Abstract: The present paper deals with a nonlinear viscoelastic equation having a dissipation term. With the equation some classical and non classical boundary conditions are combined. Based on some a priori bounds, iteration processes and density arguments, we simultaneously solve the nonlinear and the associated linear problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…In this subsection, we state, without proof, the local and global existence results for system (1), which can be proved similarly to the ones in [14,18] and [21].…”
Section: Local and Global Existencementioning
confidence: 91%
See 1 more Smart Citation
“…In this subsection, we state, without proof, the local and global existence results for system (1), which can be proved similarly to the ones in [14,18] and [21].…”
Section: Local and Global Existencementioning
confidence: 91%
“…Later, mixed problems with integral conditions for both parabolic and hyperbolic equations were studied by Pulkina [9,10], Yurchuk [11], Kartynnik [12], Mesloub and Bouziani [13], Mesloub and Messaoudi [14,15], Mesloub [16], and Kamynin [17]. For instance, Said Mesloub and Fatiha Mesloub [18] obtained existence and uniqueness of the solution to the following problem:…”
Section: Introductionmentioning
confidence: 99%
“…In Messaoudi, under suitable conditions for the relaxation function, the author showed that solutions with initial negative energy blow‐up in a limited time if p > m and remain if m ≥ p , for the following: problem uttnormalΔu+0tgfalse(tsfalse)normalΔu+utfalse|utfalse|m2=false|ufalse|p2u,in0.3emnormalΩ×false(0,false),u=0xnormalΩ,1emtfalse(0,false),ufalse(x,0false)=u0false(xfalse),1emutfalse(x,0false)=u1false(xfalse),xnormalΩ. Then, in Mesloub and Mesloub, a model describing the movement of the viscoelastic two‐dimensional body on the unit disc was investigated in the case of radial solutions. Using some prior estimates and some of the many arguments, the authors have demonstrated the existence and uniqueness of the generalized solution to the nonlocal problem utt1xfalse(xuxfalse)x+0tgfalse(tsfalse)1xxuxfalse(x,sfalse)false)xds=ffalse(x,t,u,uxfalse),in0.3emQ,uxfalse(1,tfalse)=0,1em…”
Section: Introductionmentioning
confidence: 99%
“…See the works of Cahlon and Shi and Mesloub and Lekrine, 2,3 Ewing and Lin, 4 Shi, 5 Choi and Chan, 6 Cannon, 7 Capasso-Kunisch, 8 Yurchuk, 9 Shi and Shilor, 10 Ionkin and Moiseev, 11 Kamynin, 12 Mesloub, 13,14 Ionkin, 15 Mesloub and Messaoudi, 16,17 Kartynnik, 18 Pulkina, 19,20 and Mesloub and Bouziani. 21,22 The motivation of our work is due to some results regarding the following research papers: In Mesloub, 23 the solvability of the following problem is studied…”
Section: Introductionmentioning
confidence: 99%
“…In Mesloub, 23 the solvability of the following problem is studied utt()t1x()xux()tx+0tg()ts1x()xux()x,sxds+aut()t=f()x,t,ux,u,1emin.5emQ,ufalse(x,0false)=u0false(xfalse),1emutfalse(x,0false)=u1()x,.2emx()0,1,ux()1,t=0,1em01xu()x,tdx=0.3em.1emt[]0,T, where Q:=()0,1×()0,T,1ema>01em and the bounded relaxation function g()t,1em satisfies g:++ of class C 2 such that gs0,gs…”
Section: Introductionmentioning
confidence: 99%